2021
DOI: 10.18295/squmj.2021.21.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Support Programme on Caregiver Burden Among the Family Members of Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Objectives: The family caregivers of patients undergoing coronary artery bypass graft (CABG) surgery experience considerable physical and emotional distress. This study aimed to investigate the effect of an educational support programme on caregiver burden among the family caregivers of patients undergoing CABG surgery in Iran. Methods: This non-randomised controlled clinical trial was conducted from January to April 2017 at a cardiovascular centre in Tehran, Iran. A total of 80 family caregivers of patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…However, the caregivers of the control group had more challenges, which might increase their care burden. The results obtained from different studies were similar to the present study [25,33]. Likewise, in the study by Han et al, social support reduced the social care burden of the caregivers of patients with Alzheimer's disease [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the caregivers of the control group had more challenges, which might increase their care burden. The results obtained from different studies were similar to the present study [25,33]. Likewise, in the study by Han et al, social support reduced the social care burden of the caregivers of patients with Alzheimer's disease [34].…”
Section: Discussionsupporting
confidence: 91%
“…In Iran, some studies showed that educational programmes could reduce anxiety [25] and the social health status [26] of family caregivers of patients undergoing coronary artery surgery. However, there are limited studies on the effect of training on the care burden of caregivers of patients with coronary artery bypass grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Following the increasing prevalence of coronary artery disease and the resulting mortality, coronary artery bypass graft is one of the primary and most common surgical procedures in the treatment of cardiovascular diseases, such that about 8 million people undergo CABG globally each year, about 40 000 of which are performed in Iran. ( 1 ) The advantages of CABG include alleviation of symptoms, increased survival rates, and improvements in patient function، However, many physical, mental, and social problems may occur after the operation. These problems include shortness of breath, pain in the incision area, weakness, insomnia, fear, leg edema, wound infection, palpitations, and digestive problems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, family members who are not satisfied with the intensive care service report higher levels of depression and anxiety 7 . In the literature, many studies have been conducted to determine the requirements of patients' families.…”
Section: Discussionmentioning
confidence: 99%